Pedagogical Conditions for The Development Of Mechanisms Of Communicative Competence Of Future Teachers - Makhmudova Nilufar Murotovna (Genius Journals, 2025)
The article presents scientific data on the concept of communicative competence, pedagogical conditions of mechanisms and technologies for developing communicative competence, as well as on communicative culture, communicative skills of future teachers
Keywords: communicative competence; pedagogical conditions; multimedia technologies